2023
DOI: 10.7150/thno.87363
|View full text |Cite
|
Sign up to set email alerts
|

Theranostics with photodynamic therapy for personalized medicine: to see and to treat

Youchao Wang,
Johannes Nikodemus Staudinger,
Thomas L. Mindt
et al.

Abstract: Photodynamic Therapy (PDT) is an approved treatment modality, which is presently receiving great attention due to its limited invasiveness, high selectivity and limited susceptibility to drug resistance. Another related research area currently expanding rapidly is the development of novel theranostic agents based on the combination of PDT with different imaging technologies, which allows for both therapy and diagnosis. This combination can help to address issues of suboptimal biodistribution and selectivity th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 184 publications
0
1
0
Order By: Relevance
“…Imaging based on electromagnetic radiation in the near-infrared (NIR) spectral range enables the acquisition of detailed information on the surface or interior of an object, rendering it widely applicable across various fields [ 312 , 313 ]. For instance, in medical diagnostics, near-infrared emitting nanoprobes combined with corresponding detectors can obtain images of internal lesions in human tissues or organs.…”
Section: Image Formationmentioning
confidence: 99%
“…Imaging based on electromagnetic radiation in the near-infrared (NIR) spectral range enables the acquisition of detailed information on the surface or interior of an object, rendering it widely applicable across various fields [ 312 , 313 ]. For instance, in medical diagnostics, near-infrared emitting nanoprobes combined with corresponding detectors can obtain images of internal lesions in human tissues or organs.…”
Section: Image Formationmentioning
confidence: 99%
“…This novel approach has the potential to revolutionize the field of medicine and pave the way for improved patient outcomes through individualized therapy. 443 One of the techniques for achieving personalized therapy is the utilization of biosensors that are based on graphene. These biosensors can be highly sensitive and specific in detecting various biomarkers.…”
Section: Recent Approaches Future Of Pdt and Conclusionmentioning
confidence: 99%
“…451 Graphene-based materials can also act as contrast agents to enhance the sensitivity and resolution of magnetic resonance imaging (MRI) or computed tomography (CT). 443,452,453 Zhang et al fabricated PEGylated ultrasmall GO with a chelating agent DOTA and gadolinium(III) to form GO-DOTA-Gd complexes, which showed improved T1 relaxivity. 453 Antoine et al reported that that GQDs are able to decrease the intensity of X-rays and form contrast images in both X-ray and computed tomography.…”
Section: Dovepressmentioning
confidence: 99%